2016
DOI: 10.1080/03601234.2016.1211917
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly PEG-based controlled release nano-formulations of Mancozeb: Synthesis and bioefficacy evaluation against phytopathogenic fungi Alternaria solani and Sclerotium rolfsii

Abstract: Controlled release (CR) nano-formulations of Mancozeb (manganese-zinc double salt of N,N-bisdithiocarbamic acid), a protective fungicide, have been prepared using laboratory-synthesized poly(ethylene glycols) (PEGs)-based functionalized amphiphilic copolymers without using any surfactants or external additives. The release kinetics of the developed Mancozeb CR formulations were studied and compared with that of commercially available 42% suspension concentrate and 75% wettable powder. Maximum amount of Mancoze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Easton et al (2001) reported that by the effect of Mancozeb fungicide novel proteins being induced and stress were increased. Some new technology like Nano and PEG applied for Mancozeb claimed much eco-friendly (Majumder et al 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Easton et al (2001) reported that by the effect of Mancozeb fungicide novel proteins being induced and stress were increased. Some new technology like Nano and PEG applied for Mancozeb claimed much eco-friendly (Majumder et al 2016). …”
Section: Resultsmentioning
confidence: 99%
“…There are reports that fungicides are highly effective for the control of target fungus S. rolfsii (Shirsole et al 2019). Mancozeb proved to be a broad-spectrum fungicide effective against downy mildew, collar rot, foot rot, damping-off, stem rot, root rot, southern blight, bulb rot, and wilt diseases caused by Lagenaria siceraria, Alternaria solani, Rhizoctonia solani, Sclerotium rolfsii, R. bataticola, and F. oxysporum (Majumder et al 2016;Gowari et al 2017;Bagri et al 2019;Michel-Aceves et al 2019 andVani et al 2019). Rather et al (2012) concluded that many fungicides like tebuconazole, penconazole, vitavax, hexaconazole, thiophanate methyl, and mancozeb were effective against S. rolfsii.…”
Section: Pot Trialmentioning
confidence: 99%
“…"Fungicides are mainly used to control many diseases on wide range of crops" [16,17,18]. "Mancozeb (polymeric complex of 20% Manganese and 2-5 % Zinc salt of EBDC group) is a fungicide of the carbamate pesticide family.…”
Section: Introductionmentioning
confidence: 99%